Learning Cycle 7e Model - Based Multiple Representation to Reduce Misconseption of The Student on Heat Theme - Irsyad, Muhammad; Linuwih, Suharto; Wiyanto, Wiyanto (Postgraduate, Universitas Negeri Semarang, Indonesia, 2018)
Students' success is determined by the conceptual that has been owned by the students while studying certain theme. New concepts will be elusive if the relevant concepts have not been owned by the students. Based on the observation and interview in SMP Negeri 1 Doro indicated that the heat concept is one of the elusive concept in science learning by the students. This study aims to: (1) describe the misconception experienced by students on the heat theme using a diagnostic test that is three-tier multiple choice, (2) determine the implementation of learning cycle 7E model-based multiple representation on the heat theme, (3) determine the effectiveness of the application of the learning cycle 7E model-based multiple representation in reducing misconceptions students on the heat theme. This study used a mixed method research with concurrent triangulation strategy. The identification results of students misconceptions on the heat theme obtained by average percentage of students' conceptions in the category Know the Concept (TK) is 43.44%. The average percentage of students' conceptions in the category Don’t Know the Concepts (TTK) is 15.31%. The average percentage of all misconceptions (MK) experienced by students in heat theme is 41.26%. Sub heat themes that most experienced misconceptions are ice melt events, boiling water events, heat calculations in the chart, the specific heat of water and oil, the absorption and release of heat, and the relationship of the specific heat with temperature changes. The implementation of learning cycle 7E model-based multiple representation obtained by the average percentage of 84.67% with the criteria very well. Learning cycle 7E model-based multiple representation became effective in reducing students misconceptions on the heat theme due to the decrease percentage of students misconceptions in the experimental class 18.72% is higher than the control class which only 9.68%. The analysis calculation result of the Equal Variance Assumed against independent sample of t test  towards the decrease of misconceptions level indicate significance (2-tailed) of 0.003 < 0.05, which means that there are differences in average reduction of misconceptions in the experimental class and control class.            Students' success is determined by the conceptual that has been owned by the students while studying certain material. New concepts will be elusive if the relevant concepts have not been owned by the students. Based on the observation and interview in SMP Negeri 1 Doro indicated that the heat concept is one of the elusive concept in science learning by the students. This study aims to: (1) describe the misconception experienced by students on the heat material using a diagnostic test that is three-tier multiple choice,(2) determine the implementation of learning cycle 7E model-based multiple representation on the heat material, (3) determine the effectiveness of the application of the learning cycle 7E model-based multiple representation in reducing misconceptions students on the heat material. This study used a mixed method research with concurrent triangulation strategy. The identification results of students misconceptions on the heat material obtained by average percentage of students' conceptions in the category Know the Concept (TK) is 43.44%. The average percentage of students' conceptions in the category Don’t Know the Concepts (TTK) is 15.31%. The average percentage of all misconceptions (MK) experienced by students in heat material is 41.26%. Sub heat materials that most experienced misconceptions are ice melt events, boiling water events, heat calculations in the chart, the specific heat of water and oil, the absorption and release of heat, and the relationship of the specific heat with temperature changes. The implementation of learning cycle 7E model-based multiple representation obtained by the average percentage of 84.67% with the criteria very well. Learning cycle 7E model-based multiple representation became effective in reducing students misconceptions on the heat material due to the decrease percentage of students misconceptions in the experimental class 18.72% is higher than the control class which only 9.68%. The analysis calculation result of the Equal Variance Assumed against independent sample of t test  towards the decrease of misconceptions level indicate significance (2-tailed) of 0.003 <0.05, which means that there are differences in average reduction of misconceptions in the experimental class and control class.